Upgrading corncob bio-oil via oxidative pretreatment, esterification and azeotropic distillation - Nattawut Khuenkaeo; Prapaporn Prasertpong; Nakorn Tippayawong (Cleaner Engineering and Technology)
Bio-oils produced from fast pyrolysis of agricultural residues are considered renewable without competition against food production. However, pyrolytic bio-oils are limited for direct use as fuels because of poor properties, hence, upgrading may be needed. In this study, both aqueous and organic phase bio-oils were oxidized with ozone and subsequently esterified with n-butanol or methanol in the presence of Amberlyst-15 catalyst. Ozone-UV oxidation successfully formed sufficient carboxylic acids to serve as intermediate reagent for esterification. For the organic fraction of bio-oils esterified with methanol and n-butanol accompanied by water removal, significant reduction of acids (∼75–78% total acid number and ∼53–61% of carboxylic acids) was achieved. It appeared to have lower water and oxygen content and high calorific values of 32.2–35.1 MJ/kg. The esterified aqueous fraction of bio-oils achieved high ester yield with the maximum yield of 62.5% oxygenated compounds at 1.5% catalyst loading and oxidized bio-oil to n-butanol ratio of 1:1. Although significant amount of water and oxygen was removed, the resulting liquid still had relatively low calorific value.